Methods and technologies of electroslag welding with controlled thermal cycle - Yu. V. Poletaev; V. Yu. Poletaev; A. N. Gritsyna; R. B. Aguliev (Advanced Engineering Research)
Introduction. Improving the quality and operational reliability of welded structures of power equipment is an urgent task of welding production. Its solution is possible on the basis of the development or selection of advanced methods and technologies of electroslag welding (ESW), which eliminate the causes of the formation of tempering cracks (TC) in thick-plate welds. This paper considers a comparative assessment and recommendations on the selection of such advanced ESW methods. The work objectives are to solve the problem of forming a fine-grained, uniform, crack-resistant metal structure of a welded joint with high mechanical characteristics and to reduce the negative impact of the ESW thermal cycle on the base metal. The solution to this problem is possible on the basis of a reasonable choice of methods and technologies for ESW with regulated (controlled) thermal cycle. Materials and Methods. A comparative analysis of advanced methods and technologies of ESW with a controlled thermal cycle is carried out; a comparison of their pros and cons is provided; practical recommendations on the selection of advanced methods for controlling the thermal cycle parameters are offered. Results. It is shown that moderate heat input at high-speed ESW in a narrow gap provides a single pass to form a welded joint with a finer-grained structure and high mechanical properties compared to the in-house technologies of ESW and automatic submerged-arc welding. Recommendations for practical use of the method in welding production are given. Discussion and Conclusions. The results obtained are recommended to be used in the development of ESW technology for thick-sheet welded structures of nuclear and thermal power equipment that enables to abandon postwelding heat treatment (normalization and high tempering).